5(x+2/3)=3x-2/3The answer is-2. show work so I can understand how to solve.

5(x + 2/3) = 3x - 2/3. distribute the 5 through the parenthesis

5x + 10/3 = 3x - 2/3. subtract 3x from both sides

5x - 3x + 10/3 = 3x - 3x - 2/3. combine like terms

2x + 10/3 = - 2/3. subtract 10/3 from both sides

2x + 10/3 - 10/3 = -2/3 - 10/3. simplify

2x = - 12/3. reduce

2x = - 4. divide both sides by 2

x = -4/2. reduces to -2

or this way.

5(x + 2/3) = 3x - 2/3. distribute

5x + 10/3 = 3x - 2/3. multiply by lowest common denominator of 3

15x + 10 = 9x - 2. subtract 9x from both sides

15x - 9x + 10 = -2. subtract 10 from both sides

6x + 10 - 10 = -2 - 10. simplify

6x = -12. divide both sides by 6

x = -12/6 reduces to -2

RELATED: